Pro iOS Persistence Using Core Data - Privat, Michael; Warner, Robert; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2014)
Pro iOS Persistence explains how to build apps in Objective-C and Swift that persist and use data most effectively including the popular Core Data framework. Covering common and advanced persistence patterns, this book prepares any iOS developer to store and retrieve data accurately and efficiently. This book starts by giving you a solid grounding in Core Data, providing a foundation for the rest of the book. With this knowledge, you'll have all you need to master Core Data and power your data-driven applications. You'll see how to work with SQLite and how to create an efficient data model to represent your data. Once you've established your data model, you'll learn how to work with data objects and refine result sets to get the most out of the stored data. The advanced portions of the book begin by showing you how to tune your apps' performance and memory usage, to give you a truly professional edge. You'll see how to version and migrate your data as well, to ensure your data stays organized and efficient. Finally, the book covers managing table views with NSFetchedResultsController.
Keywords: Computer science; Application software; Computer Science; Computer Science, general; Computer Appl. in Administrative Data Processing; Electronic books